Peran Pemerintah Daerah Dalam Pemberdayaan Masyarakat Nelayan di Kabupaten Pinrang - A. Sudirman Bachtiar (Departemen Ilmu Pemerintahan Fisip Unhas, 2026)
Fishing communities are coastal communities that play an important role in supporting the development of the fisheries sector and regional food security. However, various challenges such as limited human resource capacity, restricted access to technology and information, weak fishermen institutions, and the suboptimal implementation of empowerment policies continue to hinder efforts to improve fishermen's welfare. This study aims to analyze the role of the Pinrang Regency Government in empowering fishing communities. The research employed a qualitative descriptive approach using a case study method. Data were collected through interviews, observations, and documentation involving officials from the Fisheries Office, fishermen groups, and coastal communities as research informants. Data analysis was conducted through data reduction, data presentation, and conclusion drawing. The findings reveal that the Pinrang Regency Government implements fishermen empowerment through three main aspects: education and training, access to knowledge, technology and information, and institutional strengthening. Education and training programs are designed to improve fishermen’s technical skills and entrepreneurial capacity. Access to knowledge, technology, and information is facilitated through extension services, information dissemination, and the introduction of modern fisheries technologies. Meanwhile, institutional strengthening is carried out through the establishment and development of Joint Business Groups (Kelompok Usaha Bersama/KUB) as platforms for empowerment and business development among fishermen. Although several challenges remain, these empowerment efforts have contributed to improving the capacity and self-reliance of fishing communities in Pinrang Regency.